2019
DOI: 10.1200/jco.18.02374
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Phase II Study of Regorafenib in Patients With Metastatic Osteosarcoma

Abstract: PURPOSE SARC024 is a phase II clinical trial of the multikinase inhibitor regorafenib in specific sarcoma subtypes, including advanced osteosarcoma. We hypothesized that regorafenib would improve progression-free survival (PFS) in patients with sarcoma and report the results of the osteosarcoma cohort. PATIENTS AND METHODS This trial enrolled patients with progressive metastatic osteosarcoma with measurable disease by RECIST who had received at least one prior line of therapy. Patients were randomly assigned a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(159 citation statements)
references
References 19 publications
7
139
0
2
Order By: Relevance
“…Regorafenib improved disease stabilization as compared to placebo in a phase 2, randomized, double‐blind, placebo‐controlled study of adult patients with metastatic progressive OS 18 . A second randomized double‐blind phase 2 study found that regorafenib improved time to progression compared to placebo (3.6 months vs 1.7 months, respectively) in adults with progressive, metastatic OS 19 . In a clinical trial of adults with doxorubicin refractory soft tissue sarcoma, regorafenib improved progression‐free survival as compared to placebo for the nonadipocytic sarcoma subtypes studied 20 .…”
Section: Discussionsupporting
confidence: 70%
“…Regorafenib improved disease stabilization as compared to placebo in a phase 2, randomized, double‐blind, placebo‐controlled study of adult patients with metastatic progressive OS 18 . A second randomized double‐blind phase 2 study found that regorafenib improved time to progression compared to placebo (3.6 months vs 1.7 months, respectively) in adults with progressive, metastatic OS 19 . In a clinical trial of adults with doxorubicin refractory soft tissue sarcoma, regorafenib improved progression‐free survival as compared to placebo for the nonadipocytic sarcoma subtypes studied 20 .…”
Section: Discussionsupporting
confidence: 70%
“…[69][70][71][72] Recent results from the REGOBONE study (NCT02389244) and the SARC024 study (NCT02048371) report that single-agent regorafenib (pan-VEGFR small molecule inhibitor) prolonged progressionfree survival in patients with recurrent, progressive, and/or metastatic OS who have failed standard of care chemotherapy. 73,74 Both of these studies highlight the therapeutic relevance of VEGFA signaling in advanced OS. Investigating the therapeutic potential of combining antiangiogenic therapy with immune checkpoint blockade is an active area of research.…”
Section: Discussionmentioning
confidence: 98%
“…To this end, dasatinib has previously been shown to synergize with doxorubicin in vitro [28]. Finally, a recently published clinical trial of regorafenib vs placebo, (SARC024 [29]), reported increased progression free survival for pre-treated, metastatic osteosarcoma patients. We thus tested if there is an interaction between the miRNA target profile and regorafenib response and we discovered that this indeed is the case, using the previously described cut offs (coefficient >|0.15|, p<0.05).…”
Section: Pharmacogenomic Integrative Analysis Reveals Clinically Applmentioning
confidence: 99%